PHYSICAL ACTIVITIES, SITTING TIME AND FRAILTY SYNDROME IN ELDERLY (A CROSS SECTIONAL STUDY AMONG ELDER PERSON BY FRIED CRITERIA) - Sunarti, Sri; Hariyanti, Tita; Chriswantara, Riz’q Threevisca (Malang Neurology Journal, 2018)
Background. Physical activity is being a protective factor of frailty syndrome. Sedentary life style is related to frailty, comorbidities and mortality. Sitting time is associated with greater risk of dying from all causes of mortality. The correlations between physical activities, sitting time and frailty have not been studied at Indonesia.Objective. To know the correlations between physical activities, sitting time and frailty syndrome among elder person in Malang.Methods. Survey method is used in this research among elders of >60 years old in Malang. Quistionnaire-based interview was asked to respondesn and frailty measurement based on Fried’s Criteria.Results. Physical activities measured with MET (Metabolic Rate) conversely related to frailty condition in elderly and sitting time correlate well with frailty.Conclusion. Physical activities and sitting time have strong correlation with frailty in Malang.